2014
DOI: 10.3389/fnhum.2014.00752
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Tensor Magnetic Resonance Imaging for Hand and Foot Fibers Location at the Corona Radiata: Comparison with Two Lesion Studies

Abstract: The corticospinal tract is the motor pathway in the human brain, and corona radiata (CR) is an important location to diagnose stroke. We detected hand and foot motor fiber tracts in the CR to investigate accurate locations using diffusion-tensor imaging (DTI) and functional imaging. Ten right-handed normal volunteers participated in this study. We used a probabilistic tracking algorithm, a brain normalization method, and functional imaging results to set out region of interests. Moreover, our results were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…Secondly, the position of different somatotopic fibres within the PLIC overall agreed well with previous findings and neuroanatomical knowledge: Fibres originating from the non-lesional M1 representation of the hand passed almost exclusively through the dorsal two thirds of the PLIC as previously described by various neuroanatomical (Kretschmann, 1988) and neuroimaging studies (Han et al, 2010) and mostly anteriorly to the foot-related tracts (Lee et al, 2014, Kwon et al, 2014). In contrast, the corticobulbar CST fibres originating from the tongue M1 representation mostly passed through the middle or, at least for nTMS-based tractography results, central segment of the PLIC and hence most anteriorly amongst the somatotopic tracts.…”
Section: Discussionsupporting
confidence: 89%
“…Secondly, the position of different somatotopic fibres within the PLIC overall agreed well with previous findings and neuroanatomical knowledge: Fibres originating from the non-lesional M1 representation of the hand passed almost exclusively through the dorsal two thirds of the PLIC as previously described by various neuroanatomical (Kretschmann, 1988) and neuroimaging studies (Han et al, 2010) and mostly anteriorly to the foot-related tracts (Lee et al, 2014, Kwon et al, 2014). In contrast, the corticobulbar CST fibres originating from the tongue M1 representation mostly passed through the middle or, at least for nTMS-based tractography results, central segment of the PLIC and hence most anteriorly amongst the somatotopic tracts.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the DTT method, various studies have been performed to verify the characteristics of the CST including FLs, somatotopic arrangements between motor fibers, and differences in between normal subjects or patients. 2 , 8 10 , 12 , 22 , 23 However, the results from previous studies of CST somatotopy indicated some controversial issues and discrepancies due to the differences in approach and the accuracy of the analysis. In addition, interestingly, there are only few studies on finding symmetries of CST, and it is not dealt as an important issue in the research areas using DTT method although providing the symmetrical information of CST was a branch of somatotopy research considering its clinical importance for neurosurgery or neurorehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the anteriority distances for hand CST between upper CR and lower CR have some differences although they did not provide the statistical analysis results. 8 , 24 However, in our anteriority index measurement process, we defined the basis distance for the ratio using whole brain length, which is measured from the distance between the most anterior and the most posterior point of the normalized brain template structures in the CR brain level. Therefore, our results should be different from those of previous studies, and our measurement processes may also affect the statistical analysis results, although we measured the anteriority indices in a similar way to the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations